Impact of CAR and ROE on ROA in Indonesian Banking (2021–2024) - Kalishara, Kariima Monica; Manda, Gusganda Suria (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
The purpose of this research is to evaluate how the Capital Adequacy Ratio (CAR) and the Return on Equity (ROE) affect the Return on Assets (ROA) for all Indonesian Stock Exchange-listed banks (IDX)^1 from 2021 to 2024. A quantitative research method with secondary data using annual financial reports was utilized for this study. There were three types of data analysis completed in this study: descriptive statistics, classical assumption tests, and panel regression analyses. The results of this study showed no relationship between CAR and ROA. However, a significant relationship was found between ROE and ROA. Additionally, the results indicate that CAR and ROA have a significant effect on ROE. Therefore, it appears that the efficiency with which banks utilize their equity is more important than how much capital banks need; therefore, profitability for banks will be primarily determined by how well banks manage to efficiently use equity and improve return on investment from equity investees.